Screening Minors in Latin American Cinema - Osorio Nicoli, Letizia (Imagofagia, 2021)
Sobre ROCHA, Carolina e Georgia Seminet. Screening Minors in Latin American Cinema. Maryland: Lexington Books, 2014, 204pp., ISBN 978-0-7391-9951-0.